The Future of Executive Education and Training in Government Institutions: A Study on a Group of Government Institutions in the United Arab Emirates - Hammouri, Saleh Al; Ismail, Solahuddin Bin; Abualrejal, Hussein Mohammed (International Journal of Membrane Science and Technology, 2023)
This study explores the prospective trajectory of executive education and training in government institutions, focusing on a selection of government entities within the United Arab Emirates. The research delves into the evolving landscape of executive education, taking into account the rapid technological advancements, shifting social dynamics, and global challenges that influence the field. Through a comprehensive analysis of data gathered from the selected group of government institutions, the study examines various aspects of executive education, including the integration of traditional face-to-face and remote training methods. The findings offer insights into the perceptions of stakeholders regarding the significance of innovative methodologies, the impact of the COVID-19 pandemic on educational approaches, and the extent to which collaboration and access to high-quality education play a pivotal role. The research underscores the need for a balanced approach to executive education that addresses both current demands and future trends, positioning government institutions in the United Arab Emirates to effectively navigate the evolving landscape of executive education and training.